2010
DOI: 10.1074/jbc.m110.128454
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal Kinase Phosphorylation of Stathmin Confers Protection against Cellular Stress

Abstract: The cell stress response encompasses the range of intracellular events required for adaptation to stimuli detrimental to cell survival. Although the c-Jun N-terminal kinase (JNK) is a stressactivated kinase that can promote either cell survival or death in response to detrimental stimuli, the JNK-regulated mechanisms involved in survival are not fully characterized. Here we show that in response to hyperosmotic stress, JNK phosphorylates a key cytoplasmic microtubule regulatory protein, stathmin (STMN), on con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 52 publications
3
32
2
Order By: Relevance
“…JNKs phosphorylate and regulate mt-associated proteins (MAPs), consequently, JNK1-deficient mice display loss of axonal mt integrity [15]. JNKs phosphorylate the catastrophy promoting factors stathmins [16] and the protein SCG10 [17], which exhibits mt depolymerizing activity. JNKs also phosphorylate doublecortins to modulate neurite outgrowth and neuronal migration [18].…”
Section: Introductionmentioning
confidence: 99%
“…JNKs phosphorylate and regulate mt-associated proteins (MAPs), consequently, JNK1-deficient mice display loss of axonal mt integrity [15]. JNKs phosphorylate the catastrophy promoting factors stathmins [16] and the protein SCG10 [17], which exhibits mt depolymerizing activity. JNKs also phosphorylate doublecortins to modulate neurite outgrowth and neuronal migration [18].…”
Section: Introductionmentioning
confidence: 99%
“…Total cell lysates were prepared in RIPA buffer [50 mM Tris-HCl, pH 7.3, 150 mM NaCl, 0.1 mM EDTA, 1% (w/v) sodium deoxycholate, 1% (v/v) Triton X-100, 0.2% (w/v) NaF and 100 mM Na 3 VO 4 ] supplemented with protease inhibitors and immunoblotted as previously described (Ng et al, 2010) with the exception that protein lysates were resolved on SDS-PAGE without sample boiling due to the heat sensitivity of WDR62 (Wasserman et al 2010). For phosphatase treatment, lysates were prepared in RIPA buffer lacking EDTA, NaF and Na 3 VO 4 .…”
Section: Cell Lysates and Immunoblotsmentioning
confidence: 99%
“…Both MAP2 and stathmin can be phosphorylated by JNK1 and determine dendritic length and arbor complexity (Bjorkblom et al 2005;Ng et al 2010). To further understand the potential etiology for down-regulated phospho-MAP2 and phospho-stathmin in marginal ID and severe ID groups, we analyzed the The levels of FT 4 , TT 4 , FT 3 and TSH in all groups on PN7 (n = 5), PN14 (n = 8), PN21 (n = 10) and PN28 (n = 10) from the pups were measured by supersensitive chemiluminescence immunoassay.…”
Section: Marginal Id Decreased the Levels Of Phospho-jnk1mentioning
confidence: 99%
“…Stathmin is regarded as a microtubule-destabilizing factor, highly expressed in the developing nervous system (Grenningloh et al 2004). Recently, a novel discovery showed that phosphorylation by JNK1 negatively regulated the microtubule-destabilizing activity of stathmin (Ng et al 2010).…”
Section: Introductionmentioning
confidence: 99%